Characterization, stability, and in vivo effects in Caenorhabditis elegans of microencapsulated protein hydrolysates from stripped weakfish (Cynoscion guatucupa) industrial byproducts. (1st December 2021) - Oliveira Lima, Karina; Alemán, Ailén; López-Caballero, M. Elvira; Gómez-Guillén, María del Carmen; Montero, María Pilar; Prentice, Carlos; Taipe Huisa, Andy Joel; Monserrat, José Maria
Graphical abstract: Highlights: Maltodextrin was used to microencapsulate stripped weakfish protein hydrolysate. Microencapsulate protein hydrolysates were evaluated in vitro and in vivo. Microencapsulation decreased the hygroscopicity of protein hydrolysates. Microencapsulated hydrolysates showed in vitro antioxidant activity. Protein hydrolysate or microencapsulated protect in vivo from oxidative stress. Abstract: This study aimed to microencapsulate protein hydrolysates from stripped weakfish ( Cynoscion guatucupa ) industrial byproducts produced by Alcalase (HA) and Protamex (HP) by spray drying, using maltodextrin as wall material. The physicochemical characteristics, and in vitro antioxidant and Angiotensin-I converting enzyme-inhibitory activities were evaluated during storage. Both microencapsulated hydrolysates showed spherical shape (~3.6 µm particle diameter), low water activity (<0.155) during storage and reduced hygroscopicity (~30%) compared to the free hydrolysate. Infrared spectroscopy evidenced the maltodextrin-hydrolysate interaction. Based on the in vitro results, nematoid C. elegans in L1 larval stage were treated with free and microencapsulated HP, which demonstrated a protective effect on nematoid exposed to oxidative stress (survival ~ 13% control, 77% free HP, and 85% microencapsulated HP) and improved their growth and reproduction rate. Thus, microencapsulation appears to be a good alternative to maintain hydrolysates stability during storage, showing bioactivity in C. elegans .